Comportamentos de saúde, sofrimento mental e padrão de consumo de álcool entre estudantes universitários - Funai, Anderson (2019)
The objective of this study was to evaluate the relationship between health behaviors, mental distress and the pattern of alcohol consumption among college students. This is a cross-sectional study with a quantitative approach. The study involved 1,101 subjects enrolled in undergraduate courses at a federal public university of a western Santa Catarina’s state municipality. This study followed the general ethical standards of scientific research. The data collection instruments used were: sample characterization questionnaire, Youth Risk Behavior Survey, Self-Reporting Questionnaire and the Alcohol Use Disorders Identification Test. It was found that there was a predominance of female students, with a mean age of 22.7 years (standard deviation = 5.8), ranging from 18 to 65 years, white, Catholic, native of the state of Santa Catarina who were in their first year of graduation. From the sample, the main health behaviors identified were: 52.0% always wear a helmet when riding a motorcycle; 58.4% always wear seat belts; 55.7% did not hitchhike with someone who had drunk alcohol; 84.4% did not drive a vehicle in the last 30 days after drinking alcohol; 96.8% have not been beaten by their partner in the last 12 months; 97.7% were not forced to have sex; 45.7% have tried to smoke cigarettes; 18.7% were under 17 when they first smoked a cigarette; 32.3% have used marijuana in their lifetime; 6.0% have used cocaine in their lifetime; 5.2% used inhalants in their lifetime; 2.2% lifetime use of amphetamines; 8.0% use of ecstasy in life; 93.9% have already used alcohol; 29.7% make binge drinking; 21.8% have problematic alcohol use; 12.9% have had an idea of ending their lives; 36.5% have mental suffering. Mental suffering was associated with problematic alcohol use, being female, using amphetamines in life, being a student of philosophy and history courses, having no religion. Performing physical activities was a protective factor for mental distress. Problematic alcohol use was associated with mental distress, lifetime use of marijuana, and binge drinking. Being female and a medical student were characterized as a protective factor for problematic alcohol use. The results add to the available information related to health behaviors involving university students in the country.